2006
DOI: 10.1007/s00438-006-0190-0
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression dynamics in deer antler: mesenchymal differentiation toward chondrogenesis

Abstract: Annual re-growth of deer antler represents a unique example of complete organ regeneration. Because antler mesenchymal cells retain their embryonic capacity to develop into cartilage or bone, studying antler development provides a natural system to follow gene expression changes during mesenchymal differentiation toward chondrogenic/osteogenic lineage. To identify novel genes involved either in early events of mesenchymal cell specialization or in robust bone development, we have introduced a 3 K heterologous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 50 publications
(36 reference statements)
0
25
0
Order By: Relevance
“…Therefore, proteomic studies on deer followed a cross-species strategy, using a given protein database of other sequenced organism with close relative genome, analogous to the proteome profiling of Pedobacter cryoconitis [20], L. starkeyi [21] and Marenzelleria [22]. Since deer and bovine are very closely related in phylogenetics [23,24], the gene sequences of cow show high similarity (in the range 90-99%) with deer genes in the coding regions of mRNAs [25,26]. Similarly, some reports on gene expression in deer antler also revealed that the deer genes all showed high sequence homology (above 90%) to that of bovine [5,27].…”
Section: Methods Development For Efficient Protein Extractionmentioning
confidence: 99%
“…Therefore, proteomic studies on deer followed a cross-species strategy, using a given protein database of other sequenced organism with close relative genome, analogous to the proteome profiling of Pedobacter cryoconitis [20], L. starkeyi [21] and Marenzelleria [22]. Since deer and bovine are very closely related in phylogenetics [23,24], the gene sequences of cow show high similarity (in the range 90-99%) with deer genes in the coding regions of mRNAs [25,26]. Similarly, some reports on gene expression in deer antler also revealed that the deer genes all showed high sequence homology (above 90%) to that of bovine [5,27].…”
Section: Methods Development For Efficient Protein Extractionmentioning
confidence: 99%
“…As already mentioned, FGF signaling appears to be involved in the control of proliferation of the progenitor cells from the mesenchymal growth zone [11,54] . A study investigating the distribution of the de-phosphorylated form of ␤ -catenin by immunocytochemistry found the most intense staining in this zone [70] , suggesting a role for Wnt/ ␤ -catenin signaling in antler growth.…”
Section: Histo-and Morphogenesis Of the Regenerating Antlermentioning
confidence: 99%
“…FGFs are probably also involved in the control of antler growth. Thus, FGF-2 has been demonstrated to increase the proliferation rate of cultured cells from the mesenchymal growth zone of the regenerating antler [11] and a microarray study indicated that FGF signaling is activated in the antler mesenchyme [54] .…”
Section: Hard Antlers Antler Casting and Wound Healingmentioning
confidence: 99%
“…Previously we identiWed a set of genes which are diVerentially expressed during the rapid but controlled tissue proliferation (Korpos et al 2005;Molnar et al 2007;Gyurján et al 2007;Villányi et al 2008) and another set, which is involved in the skeletal physiological osteoporosis (Borsy et al 2009). In this work, we developed an antlerspeciWc cDNA microarray in order to compare gene expression levels in the tissues of the mineralizing velvet antler and the skeleton (ribs and vertebra) of deer stags.…”
Section: Introductionmentioning
confidence: 99%